Perspektif Psikologi Sosial Terhadap Perilaku Agresi di Lingkungan Sekolah - Fattah Hanurawan (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Aggression behavior is still a problem in our educational setting. School aggression involves all of the behaviors intended to harm or injure the aggression objects in the school environment. The aggression can influence teaching and learning process in the school environment. There are some social psychological theories of aggression, i.e. instinct theory, frustration aggression hypothesis theory, social learning theory. Some strategies that can prevent and reduce aggression behavior in the school are: identification of community risk factors, development prevention and intervention regulation, identification aggression potency among school’s member, punishment, catharsis and sublimation, non aggression model, and development of social skills training program.